2010
DOI: 10.1105/tpc.110.076349
|View full text |Cite
|
Sign up to set email alerts
|

DNA Replication Factor C1 Mediates Genomic Stability and Transcriptional Gene Silencing inArabidopsis   

Abstract: Genetic screening identified a suppressor of ros1-1, a mutant of REPRESSOR OF SILENCING1 (ROS1; encoding a DNA demethylation protein). The suppressor is a mutation in the gene encoding the largest subunit of replication factor C (RFC1). This mutation of RFC1 reactivates the unlinked 35S-NPTII transgene, which is silenced in ros1 and also increases expression of the pericentromeric Athila retrotransposons named transcriptional silent information in a DNA methylationindependent manner. rfc1 is more sensitive tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 87 publications
(152 reference statements)
2
62
0
Order By: Relevance
“…of the core DNA-replication proteins, including the DNA single-strand-binding protein RPA2A (Xia et al, 2006), Pola (Liu et al, 2010a), Pol « (Yin et al, 2009), POLD2 (this study), RFC1 (Liu et al, 2010b), and TOUSLED protein kinase (Wang et al, 2007). Other studies have identified other DNA replication-related proteins involved in mediating TGS, including BRU1 (Takeda et al, 2004), chromatin assembly factor (CAF-1) subunits FAS1 and FAS2 (Ono et al, 2006;Schonrock et al, 2006), and TEBICHI (Inagaki et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…of the core DNA-replication proteins, including the DNA single-strand-binding protein RPA2A (Xia et al, 2006), Pola (Liu et al, 2010a), Pol « (Yin et al, 2009), POLD2 (this study), RFC1 (Liu et al, 2010b), and TOUSLED protein kinase (Wang et al, 2007). Other studies have identified other DNA replication-related proteins involved in mediating TGS, including BRU1 (Takeda et al, 2004), chromatin assembly factor (CAF-1) subunits FAS1 and FAS2 (Ono et al, 2006;Schonrock et al, 2006), and TEBICHI (Inagaki et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, pold2-1 had little effect on the ProRD29A:LUC locus in dms3-4. Like mutants of DNA replication-related proteins (Elmayan et al, 2005;Xia et al, 2006;Yin et al, 2009;Liu et al, 2010aLiu et al, , 2010b, pold2-1 failed to suppress the silenced ProRD29A:LUC in the ros1-1 mutant (Fig. 1F).…”
Section: Isolation Of a New Component In The Drr-tgs Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…RFC1 is required for replication of the ssDNAcontaining wheat dwarf virus (WDV) genome to stimulate binding of the initiator Rep protein to 3 0 -OH containing DNA substrates (Luque et al 2002). Besides to its role as a clamp loader, RFC1 also contributes to transcriptional gene silencing of certain genes and transposons (Liu et al 2010b). …”
Section: Rfcmentioning
confidence: 99%